Just(ice) Smiling? Masks and Masking in the Occupy-Wall Street Protests - Andreas Beer (European Journal of American Studies)
The essay analyzes concepts of social justice, which were influential during the US-American Occupy protests of 2011. It discusses the recent genealogy of notions of social justice in the alter-globalization movements of the 1990s and argues that constitutive elements of Occupy’s tactics, like carnivalesque frivolity, recurred to protest forms of that decade. The essay investigates how the usage of the Guy Fawkes-mask, later associated with the comic superhero V, complicates binary logics of good and evil, arguing that such binary narratives helped in the organizational phase of the protests, but turned out to be inimical to further discussions of what constitutes social justice in the 21st century.